Bibliometric Mapping of Research on Entrepreneurial Risk-Taking Behavior - Judijanto, Loso; Wibowo, Teguh Setiawan; Apriyanto, Apriyanto; Sutanto, Himawan; Arifin , Zainal (The Es Economics and Entrepreneurship, 2024)
This study utilizes bibliometric analysis to explore the structure and dynamics of global research collaborations, particularly focusing on the field of entrepreneurial risk-taking. Utilizing data sourced from major academic databases and visualized through VOSviewer, we map the collaboration networks between countries, analyzing the roles of central hubs and their influence on global research trends. Our findings highlight the United States' pivotal role in the global research network, acting as a central hub with extensive international collaborations. The study reveals a trend toward multipolar contributions with significant inputs from countries like China, Germany, and Canada. These collaborations not only enhance the diversity and quality of research outputs but also underscore the importance of international cooperation in addressing complex global challenges. The study discusses the implications of these findings for policy-making and academic strategies, emphasizing the need to support international research collaborations to foster innovation and address global challenges effectively.